Canva-Based Interactive Media to Enhance Fourth-Grade Students’ Learning Interest in IPAS - Afdana, Alifia; Achmad, Widya Karmila Sari; Salam, Rosdiah (Jurnal Review Pendidikan Dasar : Jurnal Kajian Pendidikan dan Hasil Penelitian, 2025)
This study examined the effect of Canva-based interactive animated learning media on the learning interest of fourth-grade students in the IPAS subject. A quasi-experimental design with a Posttest Only Control Group was applied, involving 30 students divided into experimental (n = 15) and control groups (n = 15). Data were collected through questionnaires, observation, and documentation. The results of the independent samples t-test showed a significant difference in students’ learning interest between the two groups (t = 8.402, p < 0.001). The experimental group achieved a higher mean score (M = 36.53) compared to the control group (M = 26.47). The questionnaire was valid (r > 0.361, p < 0.05) and highly reliable (Cronbach’s Alpha = 0.963, indicating almost perfect internal consistency). This study contributes novelty by demonstrating that Canva, an accessible and user-friendly design platform, is effective in enhancing learning interest in primary education, differing from previous research that used specialized or less accessible media.